Production process optimization by six sigma dmaic method at black belt cold brew coffee - Nandiwardhana Pradipta, Wanda; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2016)
Abstract – Black Belt Cold Brew Coffee is a start – up business that is working on the field of beverage industry and producing the Cold Brewed coffee in a bottle. It was started on 2015 and focusing its market on Jakarta Area, and targeting the market on the Pre – work out people at the gyms or any occasions that needs a drink that has a caffeine contained served in fresh and attractive appearance. Although it is entering a considerably positive trend on the market based on its production and selling, the organization noted some threats that affecting maximization from total 4 months of selling, from 100% of production in 4 months of production there is 17% of the bottle that could not be sold. It is discovered that there is occurrence from the defects in production, such as: unmatched bottle cap (22% of whole defects), misplaced stickers (16% of whole defects), cracked bottle (19% of whole defects), broken bottle (19% of whole defects), coffee waste grounded (16% of whole defects), spoiling in pouring (8% of whole defects). To resolve the problem, it is conducted Six Sigma DMAIC Methodology and resulting the sigma level of Black Belt Cold Brew Coffee is on 2.6 – sigma or 144,791.6 defections in a million opportunity which means there is needed an improvement to reach the 6 – sigma level or 3.4 defect per million opportunity. In this process, the formulated improvement plan is to developing SOP, KPI, Product Checklist, and also implementation plan including the process timeline of control is established for any review and improvement needed along with recommendations that has been concluded. Keywords: Production Defect, DMAIC, Sigma Calculation.